(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The village panchayat is the most traditional form of local government in the Indian subcontinent. In its literal sense, the word "panchayat" refers to a group of five (or "Panch") respected and wise elders who have been elected by the people of a certain area. Historically, these assemblies have been used to resolve disagreements between communities and individuals. Local self-government was established in Bombay in 1869 when the British established a district local fund. With the formation of district local boards in 1882, Lord Ripon instituted local self-government in India. A modest attempt is made in this article, following the 73rd constitutional amendment, to identify the operational characteristics of panchayati raj entities. M. K. Gandhi’s "Gram Swaraj" and Dr. B. R. Ambedkar’s wholly opposed position on the intrinsic defects of villages that prohibit panchayats from forming as institutions of self-government dominate India’s post-independence discourse on local self-government. To better comprehend India’s contemporary panchayat governance structure, an introduction to the country’s history of local self-government before and after independence is provided. To better understand panchayats’ three-tier structure, the impediments to their efficient operation are underlined. Finding out the roles of panchayats is of limited use without enough financial decentralization. As long as those at the top of society have power, they make it hard for the poor to join in. Thus the aim of the study is to highlight the views of architect of Indian constitution on village panchayats